2011
DOI: 10.1159/000331768
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A<sub>2A</sub>-Receptor Antagonism and Pathophysiology of Parkinson’s Disease and Drug-Induced Movement Disorders

Abstract: Parkinson’s disease and drug-induced movement disorders (DIMDs) have commonalities in etiology based on impaired dopamine-based neurotransmission. Adenosine A2A-receptor antagonism may provide a new mechanism through which these disorders can be managed. In the motor circuit, tonic output from the globus pallidus and substantia nigra regulates movement via opposing excitatory and inhibitory inputs to the cerebral cortex through the direct and indirect pathways. Increased activity of the direct pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 131 publications
3
31
0
Order By: Relevance
“…These findings are consistent with previous epidemiological studies testing xanthine consumption (coffee, tea) and the risk of PD [40,41]. Thus, we hypothesize that YM may have a potential or possible protective effect in PD, which suggests that a biological component of this beverage can modify the expression, development and progression of the disease.…”
Section: Consideration Of the Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous epidemiological studies testing xanthine consumption (coffee, tea) and the risk of PD [40,41]. Thus, we hypothesize that YM may have a potential or possible protective effect in PD, which suggests that a biological component of this beverage can modify the expression, development and progression of the disease.…”
Section: Consideration Of the Methodssupporting
confidence: 92%
“…A2A receptor antagonists may confer neuroprotection against mitochondrial dysfunction and dopaminergic neuron degeneration by a direct physical interaction between the G protein-coupled A2A receptor and the receptor tyrosine kinase fibroblast growth factor receptor (FGFR) [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…A2ARs may play an important role in regulation of neurotransmission, parkinsonism, and neuroprotection, and A2A antagonists are in active therapeutic development for Parkinson's disease. 10 Given the strong involvement of A2AR in the control of inflammation, we wanted to gain insight into A2AR prevalence in the brain of SPMS patients, and used the [ 11 C]TMSX radioligand and in vivo PET imaging to evaluate this.…”
Section: Introductionmentioning
confidence: 99%
“…The A 2A adenosine receptor (A 2A R), 3 which is encoded by the Adora2a gene, is one of the most well studied G proteincoupled receptors because it is a major target of caffeine and a drug target for several brain disorders (12)(13)(14)(15). Previous studies have shown that A 2A R is widely expressed throughout the body, with the highest level of expression in the striatum (16 -20).…”
mentioning
confidence: 99%